OPTIMASI AMOBILISASI UREASE DARI Schizzosaccharomyces pombe MENGGUNAKAN MATRIK KITOSAN-NATRIUM TRIPOLIFOSFAT - Fatmawati, Ivone; Prasetyawan, Sasangka; Roosdiana, Anna (Jurnal Ilmu Kimia Universitas Brawijaya, 2013)
Determination of optimum condition of immobilized urease using chitosan-sodium tripolyphosphate has been done. Urease was isolated from Schizzosaccharomyces pombe and was purified through fractional purification method using ammonium sulphate saturation of 30– 45%. Urease is an enzyme that has the ability to hydrolyze of urea into carbon dioxide and ammonia. The activity of urease was defined as the amount of micromol ammonia per mL enzyme per minute and resulted ammonia was analyzed by spectrofotometric method using Nessler reagen. The optimum condition of immobilized urease was observed by determining the highest activity in various chitosan concentration (1.5; 2.0; 2.5; 3.0; 3.5) % w/v and urease concentration (0.840; 1.680; 2.520; 3.360; 4.200) mg/mL. The result of this experiment showed that the optimum chitosan concentration was 2.5% w/v while the optimum urease concentration was 2.520 mg/mL with the highest activity of  0.57 Units. Key words: activity, chitosan-sodium tripolyphosphate, Schizzosaccharomyces pombe, urease.